Estudo numérico da influência do enquadramento de válvulas e da recirculação dos gases de exaustão no escoamento de ar, na formação da mistura e na combustão de um motor de ignição por centelha - Fabio de Castro Radicchi (2018)
The internal combustion engines have become increasingly compact, tending to work underhighloads,whichincreasesthedemandforthecombineduseofdifferenttechnologies, such as VVT systems and EGR, mainly for knock control. Therefore, in this work the influence of the intake valves opening and closing times and the benefits of using external exhaust gas recirculation in a naturally aspirated three-cylinder internal combustion engine of twelve valves, with a volumetric compression ratio of 15:1, and a PFI system were studied. Using computational fluids dynamics, the air flow, fuel injection (E27) and spray, the process of mixture formation, and the combustion were completely characterized. Initially, an operating condition at an engine speed of 2500rpm, 4.0bar, and a 30 ABDCintakevalveclosing,correspondingtobaselineenginecondition,wassimulatedand validated by comparison with experimental data, giving credibility to the results and to the numerical methodology developed. Four operating conditions at a speed of 2500rpm and 4.36bar were then simulated, each of them using the strategy of late intake valves closing times (LIVC), corresponding to 30, 40, 50, and 70 ABDC. In addition, the operating condition at a speed of 2500rpm, 4.35bar, and LIVC 70 was also evaluated numerically using external exhaust gas recirculation, allowing a comparison of the performance achieved in this condition with the other analysis without using the external EGR. By means of the simulations, the internal recirculation of the exhaust gases was quantitatively evaluated, obtaining the maximum percentage of internal EGR correspondent to 16.11% for the condition of greater valve overlapping and 6.38% for the LIVC 70 condition. The influence of VVT on knock tolerance (KT) was also evaluated, indicating an increase for this parameter using the baseline condition, in which the valve overlapping is more significant, and a reduction of knock tolerance when reducing valve overlapping. The LIVC 70 condition was critical due to its low knock tolerance, which was overcome by using external EGR. On the other hand, the most late intake valve closing condition showed a 14% lower maximum temperature, with a consequent reduction in NO emissions. Finally, the baseline condition also presented the lowest indicated specific fuel consumption and the highest indicated power, both approximately 2% higher than the most late intake valve closing condition. Thus, the numerical data showed that the recirculationofexhaustgasesprovidesthebestresultsintermsofperformanceandknock control